Agripreneurial intention among young business graduates - Mohammad, Noorita; Shafie, Nani Ilyana; Mat Shafie, Intan Syafinaz; Badyallina, Basri; Mohammad, Mardhiah (AMH International, 2023)
The low level of public involvement in the agricultural sector in many developed and developing countries have led to a magnitude of the food security crisis. Malaysia has a large proportion of young people and has a high rate of youth unemployment. One answer is to encourage recent graduates to start businesses in the agriculture sector. This article presents data that examined the intention of the young graduate to venture into the agricultural sector, using attitude, social norms, and perceived behavioral control to solve the current food security crisis. Data was collected from young graduates who have taken business and entrepreneurship courses at the university. A self-administrated online questionnaire was designed and distributed to these young people. This study contributes to the insight into the young generation of graduates’ intention to venture into the agricultural sector as well as provides suggestions or recommendations for future studies.